Vocational students talk about texts in small groups - Reichenberg, Monica (L1-Educational Studies in Language and Literature, 2009)
The study presents a comparison between how three teachers and their students talked about texts – narrative and expository – in small groups during a regular lesson and during two lessons where a new approach of comprehension instruction, Questioning the Author (QtA), was adopted. The students were 17 years old. The majority of them were poor readers and they attended the Health Care Programme. The lessons were videotaped. During the regular lessons, the teachers dominated the text talks and mostly asked retrieve information questions. The students—including the immigrant students—made few inferences and reflections. After the regular lessons, the teachers were invited to participate in seminars led by the investigator where the QtA model was practised before videotaping the second time and the third time. Results showed that during the QtA lessons the teachers´ share of talking time diminished. The teachers´ questions also underwent changes. The number of retrieve information questions decreased and construct message questions increased. The students – includ-ing the immigrant students – read more actively during the QtA lessons. They clearly made an effort to explore ideas in the text and made numerous inferences and reflections.